Attitude of mathematics students towards integrating GCEd: a quantitative study using the tripartite attitude model - Siti Seri Kartini Mohd Yatim; Siti Ainor Mohd Yatim; Norhafizah Miswan; Muhammad Aiman Ismail (Intelektual Pustaka Media Utama, 2026)
Global citizenship education (GCEd) fosters global awareness and sustainability within mathematics education by highlighting its role in solving global challenges. This quantitative study, grounded in the tripartite attitude model, examines how mathematics students at Institute of Teacher Education Malaysia (IPGM) perceive and integrate GCEd. The 18-item questionnaire, based on the tripartite attitude model, examines emotional response, knowledge, and implementation tendency. Findings show that students generally have a positive attitude towards GCEd integration (M=4.01, SD=0.59) and recognize its importance in fostering critical thinking and social responsibility (M=4.03, SD=0.54), but their understanding remains moderate (M=3.56, SD=0.76). They emphasize the need for professional development and institutional support (M=4.20, SD=0.65) to ensure effective implementation. A significant positive correlation was found between knowledge of GCEd and attitude towards its integration (r=0.65, p0.001) suggests that deeper understanding enhances receptiveness. While students acknowledge GCEd’s value in mathematics education, additional resources and training are necessary for its successful incorporation. Strengthening support systems through targeted educational programs and institutional initiatives will better equip future educators to integrate GCEd principles, promoting global awareness and responsibility among learners.